1999
DOI: 10.1002/(sici)1097-0010(19990301)79:3<440::aid-jsfa278>3.3.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Streptomyces avermitilis CECT 3339 produces a ferulic acid esterase able to release ferulic acid from sugar beet pulp soluble feruloylated oligosaccharides

Abstract: : Sugar beet pulp (SBP) is a waste product of the sugar industry which is rich in ferulic acid. Few ferulic acid esterases (FAEs) that are capable of releasing ferulic acid from SBP or from SBP soluble feruloylated oligosaccharides (SFO-SBP) have been described. Streptomyces avermitilis CECT 3339 was grown in medium containing SBP or destarched wheat bran (DSWB) as the carbon source. FAE activity was evaluated in terms of the micro-organism's capacity to release ferulic acid from DSWB, SBP, SFO-DSWB and SFO-SB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…The molecular architecture of the cell walls of plants, and the enzymology of the degradation of the molecular structures found there, is a subject of great fundamental and practical importance 1. Cinnamoyl esterases, members of the carboxylic acid esterase class of enzymes, have been found to break the ester linkage between hydroxycinnamic acids and the attached sugar and release cinnamic acid(s) from cinnamic acid methyl esters,2, 3 feruloylated oligosaccharides,4, 5 and complex plant cell walls 6–9. These esterases act synergistically with other hydrolytic enzymes to facilitate complete degradation of the complex cell wall 10.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular architecture of the cell walls of plants, and the enzymology of the degradation of the molecular structures found there, is a subject of great fundamental and practical importance 1. Cinnamoyl esterases, members of the carboxylic acid esterase class of enzymes, have been found to break the ester linkage between hydroxycinnamic acids and the attached sugar and release cinnamic acid(s) from cinnamic acid methyl esters,2, 3 feruloylated oligosaccharides,4, 5 and complex plant cell walls 6–9. These esterases act synergistically with other hydrolytic enzymes to facilitate complete degradation of the complex cell wall 10.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the FAEs have been shown to act synergistically with xylanases, cellulases and pectinases to break down complex plant cell wall carbohydrates [4,5]. Several members of the enzyme group have been purified and characterized from aerobic and anaerobic microbes that utilize plant cell wall carbohydrates [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. These enzymes have been classified as either type A or type B, depending on their substrate specificity for aromatic moieties.…”
Section: Introductionmentioning
confidence: 99%
“…The two major FAEs of Aspergillus niger have been the focus of several studies over the last decade. However, in recent years, our knowledge of the FAE family has expanded, with reports of new enzyme activities, the characterization of gene sequences and the first crystal structure [15][16][17][18][19]29]. Molecular analysis of FAE genes and their predicted protein sequences has revealed that many of these enzymes are modular, comprising a catalytic domain translationally fused to a non-catalytic cellulose-binding domain (CBD) [15,16,19,30], or are produced as monomeric enzyme units pre-designated to be assembled into longer cohesive units, such as the cellulosome of Clostridium [31].…”
Section: Introductionmentioning
confidence: 99%
“…Ferulic acid esterase has been found to break the ester linkage between ferulic acid and the attached sugar, and so liberate ferulic acid from chemical model compounds -isolated feruloylated oligosaccharides Faulds et al 1995a, b;Williamson et al 1998a;Sancho et al 1999;Ferreira et al 1999) and from complex plant cell walls such as coastal bermudagrass ), wheat bran (Mackenzie and Bilous 1988;Williamson 1993, 1995;Relat et al 1994;Bartolomé et al 1995Bartolomé et al , 1997aFaulds et al 1995a;Kroon et al 1999), maize bran (Faulds et al 1995b), barley spent grain (Moore et al 1996;Bartolomé et al 1997a, b;Bartolomé and Gómez-Cordovés 1999;Sancho et al 1999), sugar beet pulp (Brézillon et al 1996;Ferreira et al 1999) and oat hulls (Yu et al 2000;2002a, b). Certain ferulic acid esterases have also been reported to be able to release ferulate dimers (Bartolomé et al 1997a), which play an important structural role in strengthening and cross-linking primary plant cell walls (Ishii 1997;Iiyama and Lam 2001).…”
Section: Function Of Ferulic Acid Esterasementioning
confidence: 99%
“…This latter study on ferulic acid esterase from Aspergillus niger showed that only certain substitutions on the aromatic ring can be allowed in the hydroxycinnamic acid esters and this gives specificity to this enzyme. Ferreira et al (1999) found that a purified ferulic acid esterase from Streptomyces avernitilis was capable of releasing ferulic acid from sugar beet pulp. This enzyme was also reported to have different levels of activity on methyl ferulate and methyl ρ-coumarate (releasing ferulic and ρ-coumaric acids), but no activity was observed on methyl caffeate.…”
Section: Specificity Of Purified Ferulic Acid Esterase Specificity Ofmentioning
confidence: 99%